Kesalahan Berbahasa Bidang Fonologi pada Akun Youtube Nihongo Mantappu: “Wasedaboys jadi Guru Jepang di SMA Indonesia! Gimana Ya!?” - Setiawan, Aldi; Damastina, Biona (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
The aim of this research is to explain language errors at the phonological level in the Nihongo makanpu YouTube account videos by using the example of the video entitled